(untitled) (Majalah Kedokteran Bandung, 2026)
Diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia resulting from impaired insulin secretion or insulin action. Dyslipidemia is a common complication of DM and is associated with an increased risk of cardiovascular disease. Although pharmacological therapies are widely used, their long-term use is often limited by adverse effects, highlighting the need for safer alternative therapeutic approaches. The butterfly pea (Clitoria ternatea L.) has been reported to possess antidiabetic and antioxidant properties; however, evidence regarding its effects on inflammatory mediators such as TNF-α and Gys gene expression in diabetic–dyslipidemic conditions remains limited. This study aimed to evaluate the modulatory effects of C. ternatea extract (CTE) on TNF-α expression and Gys gene expression in diabetic–dyslipidemic rats. This experimental study was conducted from July to September 2021 in Bogor and Bandung, Indonesia. Diabetic–dyslipidemic rats were attained by inducing streptozotocin (STZ) and a high fat diet (HFD). CTE was administered at doses of 200, 400, and 800 mg/kg body weight. Glibenclamide, simvastatin, and their combination were administered to diabetic rats as a comparison group. The immunohistochemistry assay was conducted to quantify liver TNF-α protein expression, and liver and muscle’s Gys genes were determined by quantitative qRT-PCR. Results showed 800 mg/kg BW CTE had a positive effect on decreasing TNF-α expression and elevating liver and femoral muscle Gys expression. Butterfly pea extract has the potential as an antidiabetic by regulating TNF-α and Gys gene.